Effect of manganese dioxide on the formation of humin during different agricultural organic wastes compostable environments: It is meaningful carbon sequestration. (March 2020) - Qi, Haishi; Zhao, Yue; Zhao, Xinyu; Yang, Tianxue; Dang, Qiuling; Wu, Junqiu; Lv, Pin; Wang, Hua; Wei, Zimin
Graphical abstract: Highlights: MnO2 facilitated humin formation, especially in lignocellulose-rich materials. Degradation of organic components was accelerated by the addition of MnO2 . The formation mechanism of humin was identified. The role of MnO2 in the formation of humin content was identified. Abstract: The study aims to accelerate the formation of humin (HM) with the addition MnO2 to achieve carbon sequestration during different material composting. The results indicated that the addition of MnO2 could improve the concentration of HM by increasing of the content in functional groups during corn straw (CS) and chicken manure (CM) composting. With the addition of MnO2, non-aromatic functional groups were responsible for the increase of the HM concentration in CM, while aromatic functional groups were dominating for CS. Although the formation mechanism of HM varied significantly across different materials, the MnO2 promoted more abundant functional groups to participate the formation of recalcitrant fluorescence components in CS and CM. In addition, the aromatization of HM structure was improved by adding the MnO2 . Therefore, the addition of MnO2 not only increase carbon sequestration but also increase the compost product resilience during the decompose of agricultural organic wastes.